New syllabus primary mathematics 4B 2nd edition workbook - Dr Yee , Foong Pui; Hui , Chang Suo (Karachi : Oxford University Press, 2024)
The Primary Mathematics Workbook 4A (2nd Edition), following the Singapore Math methodology, is designed for fourth-grade students and serves as a supplement to the Primary Mathematics 4A Textbook. It employs the concrete-pictorial-abstract approach to develop a solid understanding of mathematical concepts. The workbook covers topics such as large numbers (up to 100,000), advanced operations (addition, subtraction, multiplication, division), factors and multiples, fractions, and angles. Emphasis is placed on problem-solving, using visual models like bar diagrams, to build students$1 (Blogical reasoning and analytical skills. The workbook encourages deep comprehension through ample practice, preparing students for more complex mathematical challenges.s
Keywords: Mathematics - workbook; Oxford Matthematics - workbook